Performance evaluation of new waterborne epoxy resin modified emulsified asphalt micro-surfacing. (30th July 2019) - Liu, Mengmei; Han, Sen; Wang, Zhaoyu; Ren, Wanyan; Li, Wei
Highlights: The new binder of WEREA was introduced to micro-surfacing mixtures. WEREA micro-surfacing mixtures design was studied. Early pavement performance and durability of WEREA micro-surfacing were satisfactory. Abstract: Micro-surfacing is an available choice for pavement preventive maintenance. This paper introduced a new micro-surfacing using developed Waterborne Epoxy Resin (WER) modified emulsified asphalt to overcome the common distress, such as abrasion, rutting, ravelling and poor durability. The skid resistance, bonding, rutting and wear performances of different formulations of the proposed micro-surfacing materials were compared with Styrene Butadiene Rubber (SBR) modified micro-surfacing by load wheel tests, wet track abrasion tests, skid resistance tests, load wheel tracking tests, cantabro tests and accelerated loading tests. Results indicated that WER could improve the early pavement performance of micro-surfacing significantly, especially their bonding and rutting resistance. WER also produced improved durability performance. The damage in the critical condition of water immersion, freeze–thaw and heavy traffic was alleviated greatly by the use of WER. Therefore, it can be concluded that WER modified emulsified asphalt is a good binder for micro-surfacing.